Kinetic and Isotherm Modeling of Adsorption of Dyes onto Sawdust - K. Shakir, Ibtehal (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
Sawdust has the ability to adsorb the dyestuff from aqueous solution. It may be useful low cost adsorbent for the treatment of effluents, discharged from textile industries. The effectiveness of sawdust has been tested for the removal of color from the wastewater samples containing two dyes namely Direct Blue (DB) and Vat Yellow (VY). Effect of various parameters such as agitation time, adsorbent dose and initial concentration of each dye has been investigated in the present study. The adsorption of dyes has been tested with various adsorption isotherm models. The Langmuir isotherms model is found to be the most suitable one for the dye adsorption using sawdust and the maximum adsorption capacity is 8.706 mg/g and 6.975 mg/g for DB and VY respectively. The adsorption process is best described by second-order kinetics and the corresponding rate constants (K2) are obtained which are found to be 0.2837g/mg.min and 0.1274 g/mg.min for DB and VY respectively at the maximum concentration.